Tales of three worlds - archaeology and beyond: Asia, Italy, Africa archaeology and beyond : a tribute to Sandro Salvatori - Usai, Donatella; Tuzzato, Stefano; Vidale, Massimo 1956- (Archaeopress Publishing Ltd, 2020)
This book presents a series of papers in honour of Sandro Salvatori divided into three main sections reflecting his long years of work in Middle Asia, his time in Italy as an officer of the Archaeological Superintendency (Ministry of Cultural Heritage), and finally his studies on the prehistory of north-eastern Africa
Keywords: Electronic books; Festschrift